What should accountable care organizations learn from the failure of health maintenance organizations? A theory based systematic review of the literature - Amir Alishahi Tabriz; Elham Nouri; Huyen T Vu; Van T. Nghiem; Brandt Bettilyon; Pooriya Gholamhoseyni; Nazanin Kiapour (Shahid Beheshti University of Medical Sciences, 2017)
Background: Health Maintenance Organization (HMO), were once viewed as the most cost-effective model for achieving such efficient high-quality health care. A decade after the decline of HMOs a similar idea evolves and continues to proliferate under the rubric of Accountable Care Organizations (ACOs). Methods: We performed a systematic review according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses to identify the reasons for the decline of HMOs, with the ultimate goal of extrapolating findings from HMOs experiences onto ACOs. We searched PubMed, Web of Science, and EMBASE to select original research and reports related to the decline of HMOs in the U.S. Using organizational evolving theory the contents of selected studies were analyzed and categorized according to common characteristics. Results: Although the decline of HMOs varies somewhat from case to case, it follows a fairly consistent pattern with similar causes. These factors were related to wrong ethos, mismanagement, failing to control costs, resistance from provider groups, increased competition, and inadequate IT infrastructure leading to patient dissatisfaction. Patient dissatisfaction in turn led to a managed care backlash, which stimulated the enactment of new restrictive legislation. Restrictive legislation not only negatively impacted the continued growth of HMOs but also accelerated the speed of their decline. Conclusion: ACOs should set realistic goals, align the incentives for physicians and hospitals via shared savings, use non-physician providers such as nurse practitioners, invest on health information technology, practice patient centered approach, make provider and patients accountable, use efficient management methods and improve care coordination.